The Design of an Anti-Aliasing Filter for the Next Generation Digitiser - Theunissen, Edroy (Department of Electrical Engineering, 2023)
MeerKAT, is a 64-element radio astronomy antenna array which has been recently constructed in the Northern Cape Province of South Africa. It serves as South Africa's contribution towards the international Square Kilometre Array (SKA) project. The MeerKAT array has been designed to observe radio signals produced by celestial sources at UHF-Band, L-Band, S-Band and X-Band frequencies. The first phase of the construction included the design, development and integration of the UHF-Band, L-Band and S-band Receivers, whilst the X-band design has been superseded by the incorporation of the next phase of the SKA international project. In preparation of the next the roll-out, research is required to determine optimal wideband filter topologies suitable for direct digitisation of signal frequencies over the frequency range of 3-6 GHz. In this thesis, exploration of suitable wideband planar filters is performed, noting those with an improved out-of-band rejection. The outcome of the investigation leads into the design and development of the suitable wideband planar filter based on key performance specifications. The performance of the manufactured wideband planar filter is then compared to the theoretical design, and validated against the key performance requirements.